Responses of grape berry anthocyanin and tritratable acidity to the projected climate change across the Western Australian wine regions - Barnuud, N.; Zerihun, Ayalsew; Mpelasoka, F.; Gibberd, Mark; Bates, B. (Springer, 2013)
More than a century of observations has established that climate influences grape berry composition. Accordingly, the projected global climate change is expected to impact on grape berry composition although the magnitude and direction of impact at regional and subregional scales are not fully known. The aim of this study was to assess potential impacts of climate change on levels of berry anthocyanin and titratable acidity (TA) of the major grapevine varieties grown across all of the Western Australian (WA) wine regions. Grape berry anthocyanin and TA responses across all WA wine regions were projected for 2030, 2050 and 2070 by utilising empirical models that link these berry attributes and climate data downscaled (to ∼5 km resolution) from the csiro_mk3_5 and miroc3_2_medres global climate model outputs under IPCC SRES A2 emissions scenario. Due to the dependence of berry composition on maturity, climate impacts on anthocyanin and TA levels were assessed at a common maturity of 22 °Brix total soluble solids (TSS), which necessitated the determination of when this maturity will be reached for each variety, region and warming scenario, and future period.The results indicate that both anthocyanin and TA levels will be affected negatively by a warming climate, but the magnitude of the impacts will differ between varieties and wine regions. Compared to 1990 levels, median anthocyanins concentrations are projected to decrease, depending on global climate model, by up to 3–12 % and 9–33 % for the northern wine regions by 2030 and 2070, respectively while 2–18 % reductions are projected in the southern wine regions for the same time periods. Patterns of reductions in the median Shiraz berry anthocyanin concentrations are similar to that of Cabernet Sauvignon; however, the magnitude is lower (up to 9–18 % in southern and northern wine regions respectively by 2070). Similarly, uneven declines in TA levels are projected across the study regions. The largest reductions in median TA are likely to occur in the present day warmer wine regions, up to 40 % for Chardonnay followed by 15 % and 12 % for Shiraz and Cabernet Sauvignon, respectively, by 2070 under the high warming projection (csiro_mk3_5). It is concluded that, under existing management practices, some of the key grape attributes that are integral to premium wine production will be affected negatively by a warming climate, but the magnitudes of the impacts vary across the established wine regions, varieties, the magnitude of warming and future periods considered.